Characteristics of EMS Fellowships in the United States. (2nd January 2023) - Flamm, Avram; Burch, Kyle; Lubin, Jeffrey; Mencl, Francis
Abstract: Background: EMS was recognized as a subspecialty of Emergency Medicine in 2010. Accreditation of EMS fellowship programs started in 2013. Despite increasing numbers of programs and a decade since recognition, little has been written about the characteristics and offerings of these programs. Methods: A 24-question electronic survey was distributed to US accredited programs in spring 2020. Data were analyzed using descriptive statistics. Results: Ninety percent (61/68) of programs participated. Most offer two spots, an urban (89%) and/or suburban (62%) experience, with 3–12 faculty (M = 5.9, 95% CI [5.34–6.49]), physician response vehicles (59%), and aeromedical exposure (95%). Many programs train in field amputation (72%), but fewer train in field thoracotomy (49%), prehospital ultrasound (64%) and ECMO cannulation (15%). Disaster planning experience is provided mostly with hospitals (87%) or EMS agencies (85%). Most (72%) mass gathering experiences are marathons or concerts involving 1, 000–24, 999 participants, but 20 programs (33%) participate in events with >100, 000 participants. Special operations training includes tactical (75%), fireground (52%), wilderness (39%), and international EMS (56%), but only 12% offer rotation outside the US. About half (46%) include experience with community paramedicine, and 31% are developing an ET3 program. Nearly all programs (98%) involve fellows in simulation, but only 38% provide instruction in how to teach with simulation. All fellows see patients in the ED, with 75% supervising residents. In 7%, the fellow works under a supervising attending much like a resident. In 2019–20, 28% of programs had at least one unfilled position and 15% went completely unfilled, yet, this was not correlated with any specific program characteristic. Conclusions: Despite some commonality, especially in required experiences, considerable differences exist between programs in how education is delivered. However, none of them correlate with filling or the size of the program. Involvement in unique areas such as ultrasound or community paramedicine was not universal. It is unclear what if any impact these differences have on career preparation and satisfaction. Programs may wish to consider sharing resources to offer future EMS physicians more comprehensive experiences.